2006
DOI: 10.1542/peds.2005-2326
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Infants Who Are Younger Than 2 Months During Suprapubic Aspiration and Transurethral Bladder Catheterization: A Randomized, Controlled Study

Abstract: In infants who are younger 2 months, suprapubic aspiration is more painful than transurethral catheterization. Health professionals should consider these differences when choosing a method for obtaining a urine sample from young infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 29 publications
3
51
0
Order By: Relevance
“…In the previous technical report, SPA was reported to have success rates ranging from 23% to 90%, 22-24 although higher success rates have been achieved when SPA is conducted under ultrasonographic guidance. 25,26 SPA is considered more invasive than catheterization and, in RCTs from 2006 27 and 2010, 28 pain scores associated with SPA were significantly higher than those associated with catheterization. This result was found for both boys and girls.…”
Section: Obtaining a Urine Samplementioning
confidence: 99%
See 1 more Smart Citation
“…In the previous technical report, SPA was reported to have success rates ranging from 23% to 90%, 22-24 although higher success rates have been achieved when SPA is conducted under ultrasonographic guidance. 25,26 SPA is considered more invasive than catheterization and, in RCTs from 2006 27 and 2010, 28 pain scores associated with SPA were significantly higher than those associated with catheterization. This result was found for both boys and girls.…”
Section: Obtaining a Urine Samplementioning
confidence: 99%
“…Similar to previous studies, these RCTs also revealed lower success rates for SPA (66% and 60%), compared with catheterization (83% and 78%). 27,28 In comparison with SPA results, cultures of urine specimens obtained through catheterization are 95% sensitive and 99% specific. 7,11,12 Cultures of bag specimens are difficult to interpret.…”
Section: Obtaining a Urine Samplementioning
confidence: 99%
“…Staff were excluded if they worked less than 20 h per week or had worked for less than 12 months in their disciplinary area, and/or had a history of a neurological, psychiatric or pain-related illness for which they required regular medication. Based on the work of Kozer et al (27), a sample size of 25 in each group was required to detect a difference of two points on the Douleur Aigue Nouveau (DAN) pain scale (28) between the nurse and non-nurse groups, with a power of 0.80 and an α of 0.05. Twenty-five participants from both groups were randomly selected from lists provided by unit managers using a random numbers …”
Section: Objectives and Hypothesesmentioning
confidence: 99%
“…Another consideration, however, is that suprapubic catheterization seems to be more painful than transurethral catheterization in infants younger than 2 months. 5 Diagnostic confirmation is not required, as this is the criterion standard test. Ultrasound guidance can be used in the case of an unsuccessful tap.…”
Section: Evidence and Diagnostic Confirmationmentioning
confidence: 99%